2021
DOI: 10.17085/apm.21025
|View full text |Cite
|
Sign up to set email alerts
|

Pre-operative fasting times for clear liquids at a tertiary children’s hospital; what can be improved?

Abstract: Background: The goal of preoperative fasting is to prevent pulmonary aspiration during general anesthesia. Fasting times are often prolonged leading to patient discomfort and risk for adverse events. This retrospective quality improvement survey evaluated effective nil-per-os (NPO) times and causes for prolonged NPO times with the aim to suggest improvement strategies by a newly founded fasting task force.Methods: Data from all electronic anesthesia records from 2019 at our institution were reviewed for fastin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…However, the problem of the separation of theory and practice lies. Fasting time from drinking is di cult to control accurately, and most of the time there is a delay, mainly due to parental concerns, and surgical anesthesia departmental articulation (9,13). In A J Kouvarellis' study, it was similarly found that there was a large discrepancy between clinical and guidelines and that systematic quality improvement was needed to make it possible to reduce the discrepancy (14).…”
Section: Discussionmentioning
confidence: 99%
“…However, the problem of the separation of theory and practice lies. Fasting time from drinking is di cult to control accurately, and most of the time there is a delay, mainly due to parental concerns, and surgical anesthesia departmental articulation (9,13). In A J Kouvarellis' study, it was similarly found that there was a large discrepancy between clinical and guidelines and that systematic quality improvement was needed to make it possible to reduce the discrepancy (14).…”
Section: Discussionmentioning
confidence: 99%
“…16 Its significance can be distilled into aspects such as safeguarding organ functionality, ensuring anesthesia safety, guiding effective medical care, optimizing surgical precision, accelerating postoperative recovery, diminishing morbidity and mortality, fortifying infection control. 13,17 All patients scheduled for surgery should be monitored, but the degree of monitoring can vary. Hemodynamically stable patients require maybe nothing more than continuous electrocardiographic (ECG) monitoring, regular non-invasive blood pressure measurement, and peripheral pulse oximetry (Spo2).…”
Section: Anesthesia (Esa) (2011) Have Been Publishedmentioning
confidence: 99%
“…Further, Schmidt et al. highlighted how wordings for a ‘nil by mouth’ instruction can lead to parents fasting children for longer than necessary, due to worries about surgery being cancelled [22]. Changing the instruction from punitive statements to those of encouragement, and highlighting the benefit of following the advice closely, can improve parent's understanding and engagement.…”
Section: Real Worldmentioning
confidence: 99%